COVID-19 vaccines provide better protection against related pneumonia than previous symptomatic infection - Efrén Murillo-Zamora; Xóchitl Trujillo; Miguel Huerta; Mónica Ríos-Silva; José Guzmán-Esquivel; Verónica Benites-Godínez; María Regina Ochoa-Castro; José Alejandro Guzmán-Solórzano; Oliver Mendoza-Cano (International Journal of Infectious Diseases, 2022)
Objectives: To compare, in a real-world scenario, the protective effect of vaccination and previous laboratory-confirmed symptomatic infection on the risk of COVID-19 pneumonia. Methods: A retrospective study was conducted and 46,998 adults with laboratory-confirmed COVID-19 were enrolled. Risk ratios (RRs) and 95% confidence intervals (CIs) were used to evaluate the effect of the evaluated exposures on the risk of pneumonia. Results: In multiple analysis and after adjusting by reinfection status, vaccinated participants were at reduced risk of developing pneumonia (RR = 0.974, 95% CI 0.965–0.983). The association of having had a previous infection was not significant (RR = 1.001, 95% CI 0.969–1.034). Conclusion: Our results suggest, and if later replicated, that COVID-19 vaccines provide better protection against pneumonia than previous symptomatic infections. Therefore, offering vaccination to all eligible subjects despite past COVID-19 infections might be relevant to reducing the pandemic-related burden.